Mapping graphic navigational systems - Fawcett-Tang, Roger; Owen, Williams (Mies; Hove RotoVision, 2008)
Offers a study of the various areas of cartography from nautical charts to subway systems, from websites to calendars. This guide reveals the visual language of location, direction, spatial and structural relationships which are central to the information design discipline. It is intended for professional information designers and design students.
Keywords: Cartography -- Data processing -- case studies; Geographic Information system; Cartography; Graphic arts; Computer arts